Australian water quality trends over two decades show deterioration in the Great Barrier Reef region and recovery in the Murray-Darling Basin - Danlu Guo; Qian Zhang; Camille Minaudo; Rémi Dupas; Clément Duvert; Shuci Liu; Kefeng Zhang; Ulrike Bende-Michl; Anna Lintern (Communications Earth & Environment)
Abstract Understanding river water quality trajectories and drivers is crucial for effective environmental management. Here we present a comprehensive nation-wide water quality trend assessment across Australia with 287 catchments from 2000 to 2019. About half of the catchments show significant trends in the flow-normalised concentration for each parameter analysed. Most of these significant trends are due to changes in concentration-flow relationships rather than long-term trends in flow. Two of Australia’s major river basins show opposing regional patterns in their significant trends. The North East Coast, which largely flows into the Great Barrier Reef lagoon, has increasing phosphorus and sediments. This potentially reflects lagged effects of increasing land clearing and fertilisation since 1960s, while land improvement in the region has not yet demonstrated improvement on water quality. The Murray-Darling Basin has decreasing salinity, phosphorus, and sediment, likely driven by effects of a region-scale salinity management interventions and a prolonged drought on catchment processes.